A convolutional neural network with pixel-wise sparse graph reasoning for COVID-19 lesion segmentation in CT images. (March 2023) - Jia, Haozhe; Tang, Haoteng; Ma, Guixiang; Cai, Weidong; Huang, Heng; Zhan, Liang; Xia, Yong
Abstract: The COVID-19 pandemic has extremely threatened human health, and automated algorithms are needed to segment infected regions in the lung using computed tomography (CT). Although several deep convolutional neural networks (DCNNs) have proposed for this purpose, their performance on this task is suppressed due to the limited local receptive field and deficient global reasoning ability. To address these issues, we propose a segmentation network with a novel pixel-wise sparse graph reasoning (PSGR) module for the segmentation of COVID-19 infected regions in CT images. The PSGR module, which is inserted between the encoder and decoder of the network, can improve the modeling of global contextual information. In the PSGR module, a graph is first constructed by projecting each pixel on a node based on the features produced by the encoder. Then, we convert the graph into a sparsely-connected one by keeping K strongest connections to each uncertainly segmented pixel. Finally, the global reasoning is performed on the sparsely-connected graph. Our segmentation network was evaluated on three publicly available datasets and compared with a variety of widely-used segmentation models. Our results demonstrate that (1) the proposed PSGR module can capture the long-range dependencies effectively and (2) the segmentation model equipped with this PSGR module can accurately segment COVID-19 infected regions in CT images and outperform all other competing models. Graphical abstract: Highlights: Propose pixel-wise sparse graph reasoning (PSGR) for COVID-19 CT image segmentation. Project the image features pixel-wisely to graph space for global information reasoning. Design an edge pruning strategy for the constructed graph to retrieve effective information. Achieve the state-of-the-art performance on three public COVID-19 CT datasets.